Evaluating the technical and economic aspects of thermal performance of extensive green roofs: A GIS-based case study in the urban setting of Na- dor, Morocco - Rachid Lambarki; Elmostafa Achbab; Mehdi Maanan; Hassan Rhinane (Chinese Journal of Population, Resources and Environment)
The increasing demand for green spaces in cities underscores the urgent need for sustainable solutions to reduce the ecological impact of urban areas. This research focuses on converting unused rooftops into extensive green roofs in Nador, Morocco, offering an innovative approach to enhancing outdoor thermal comfort in this region. Several advanced techniques were used, including photogrammetric restitution (for creating land use maps), integration of light detection and ranging data (for three-dimensional urban modeling), and meteorological data collection (for modeling urban climate conditions). The urban-multiscale-environmental-predictor solar and longwave environmental irradiance geometry (UMEP-SOLWEIG) model was crucial for precisely evaluating the thermal performance of green roofs and their influence on urban microclimates. This model considers considered various parameters, such as the sky view factor, wall height and aspect, and shading conditions, for accurate, comprehensive analysis. Additionally, for accurate, comprehensive analysis, a comparative evaluation was performed between the UMEP-SOLWEIG and ENVI-met models to assess the UMEP-SOLWEIG results. The findings were notable, demonstrating a substantial reduction (averaging over 3 °C) in the mean radiant temperature on 60% of rooftops, covering 55% of the total surface area. This highlighted the effectiveness of green roofs in improving outdoor thermal comfort. Furthermore, green roofs were closely associated with reductions in air-conditioning energy consumption, with considerable reductions ranging from 17.53% to 43.82%. These savings translated to estimated financial benefits ranging from USD 1.63–4.07 million. These figures clearly verified the notable economic impact of green roofs despite their initially high costs (approximately USD 84.44 million). These potential long-term savings indicated that these investments are financially viable in the long run. The collected data were used to create thermal maps of the area using geographic-information-system tools. A thermal cadaster specific to green roofs was also developed, accessible online through Web mapping. Overall, this approach facilitates decision-making in urban planning by providing visual information on thermal variations, thereby aiding in the precise planning of measures against urban heat and promoting the use of green roofs to reduce environmental impact.